Cold war Canada : the making of a national insecurity state, 1945-1957 - Whitaker, Reginald, 1943- (CEL - Canadian Publishers Collection., 1994)
Canadians might expect that a history of Canada's participation in the Cold War would be a self-congratulatory exercise in documenting the liberality and moderation of Canada set against the rapacious purges of the McCarthy era in the United States. Though Reg Whitaker and Gary Marcuse agree that there is some evidence for Canadian moderation, they argue that the smug Canadian self-image is exaggerated.